Evaluasi Pertumbuhan dan Produksi serta Seleksi Tanaman Jagung Generasi F1-F2 Hasil Persilangan Jagung Manis dengan Jagung Ungu - Halimi, E. S.; Wulandari, A.; Adriansyah, F.; Andesta, M. (Seminar Nasional Lahan Suboptimal, 2024)
Halimi, E. S., A. Wulandari., F. Adriansyah., & M. Andesta. (2024). Evaluation on growth production and selection of  corn plants generation f1-f2 from the cross of  sweet and purple-corn. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang  21 Oktober 2024. (pp. 323–334).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Sweet-corn  is a popular agricultural product in Indonesia, most of  the varieties are yellow, white and not as purple. This research was to part of plant breeding program to evaluate the growth of F1-generation seeds and develop sweet corn varieties have high brix-levels and are purple in-color. Prior to this research crossing was made between sweet-corn variety as female and purple-corn as male parent. In this research, the F1-seeds resulted for that cross were planted along with the remnant-seeds of female parent in a Randomized Block Design. The research utilized dual-planting system, each to produce baby and sweet-corn and one other remaining plants were maintained to produce dry-seed. The research results avarage plant-heigh was 271.71 cm, male and female anthesis were at 46-days and 50-days. The baby-corns were harvested at 54-days, with avarege fresh-weight of 27.70 g/cob with sugar content of 4.5 %brix and the sweet-corn were harvested at 73-days, with average fresh-weight of 29440 g/cob and sugar content of 12.5 %brix. Special observation on sugar-content of  sweet-corn having purple seed resulted in 7.5 %brix as compare to population average of 12.5 %brix and the famale parent of 13.0 %brix. The seeds-color, however, were segregated to be yellow, white, and purple. Selection of-seeds from dry-cobs resulted in 10 purple-seeds cobs, among which 916 grains have a-wrinkled texture. These seeds could be good genetic material for next reaseacrh to develop new purple sweet-corn variety. Result of this research indicated that F1-plants were capable to-grow and produce baby-corn, sweet-corn, as-well as F2-generation seeds well.